2003
DOI: 10.1002/sce.10063
|View full text |Cite
|
Sign up to set email alerts
|

Understandings of the nature of science and decision making on science and technology based issues

Abstract: ABSTRACT:The purpose of this investigation was to explicate the role of the nature of science in decision making on science and technology based issues and to delineate factors and reasoning associated with these types of decisions. Twenty-one volunteer participants purposively selected from the faculty of geographically diverse universities completed an open-ended questionnaire and follow-up interview designed to assess their decision making on science and technology based issues. Participants were subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
183
0
66

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(262 citation statements)
references
References 33 publications
(51 reference statements)
13
183
0
66
Order By: Relevance
“…It is under these characteristics and with these theoretical elements in which different organizations, either implicitly or explicitly, face their different needs to confront evolution or change processes, where the simple availability of scientific and technical information is not always enough to make good decisions (Bell and Lederman, 2003;Pidgeon and Fischhoff, 2011). Now, we shall review how climate change appears as a new relevant element within this context, with its own characteristics, difficulties and challenges.…”
Section: • Evaluation Of Resultsmentioning
confidence: 99%
“…It is under these characteristics and with these theoretical elements in which different organizations, either implicitly or explicitly, face their different needs to confront evolution or change processes, where the simple availability of scientific and technical information is not always enough to make good decisions (Bell and Lederman, 2003;Pidgeon and Fischhoff, 2011). Now, we shall review how climate change appears as a new relevant element within this context, with its own characteristics, difficulties and challenges.…”
Section: • Evaluation Of Resultsmentioning
confidence: 99%
“…Some of the students comprising this group were able to recognize data without the ability to describe its use or significance, whereas others could not even distinguish among data, unfounded opinions, and predictions. Bell and Lederman (2003) have examined the reasoning patterns of university professors representing various fields (including science educators, science philosophers, and research scientists) on SSI and found similar reasoning patterns among these groups, including emphases on personal philosophy and commitments over reasoning based on scientific evidence. Although the participants of this study held varied views of the NOS, their decision-making strategies and actual decisions on science and technology-based issues yielded no discernable patterns unique to particular NOS views.…”
Section: Thematic Areas Of Recent Research Connected To Ssimentioning
confidence: 99%
“…The three socioscientific scenarios were sourced from a set of four scenarios, and associated questions developed by Bell and Lederman (2003). The Decision Making Questionnaire ''DMQ'' was designed to obtain information about participants' reasoning in a variety of socioscientific contexts, and the scenarios were contextually linked to relevant scientific concepts addressed in the course.…”
Section: Nosmentioning
confidence: 99%
“…Previous research has indicated that participants possess both general epistemologies of knowledge, and specific scientific epistemologies. Bell and Lederman (2003) proposed that the decisions made by participants in their study on a selection of socioscientific issues may have reflected their general epistemologies of knowledge, rather than their specific scientific epistemologies. In this study, Tom and Sarah possessed relatively stronger background scientific knowledge than Rachel, Monica, and David.…”
Section: Contextual Factorsmentioning
confidence: 99%